Cognitive mapping style relates to posterior–anterior hippocampal volume ratio. Issue 8 (3rd February 2019) - Brunec, Iva K.; Robin, Jessica; Patai, Eva Zita; Ozubko, Jason D.; Javadi, Amir‐Homayoun; Barense, Morgan D.; Spiers, Hugo J.; Moscovitch, Morris
Abstract: As London taxi drivers acquire "the knowledge" and develop a detailed cognitive map of London, their posterior hippocampi (pHPC) gradually increase in volume, reflecting an increasing pHPC/aHPC volume ratio. In the mnemonic domain, greater pHPC/aHPC volume ratios in young adults have been found to relate to better recollection ability, indicating that the balance between pHPC and aHPC volumes might be reflective of cross‐domain individual differences. Here, we examined participants' self‐reported use of cognitive map‐based navigational strategies in relation to their pHPC/aHPC hippocampal volume ratio. We find that greater reported cognitive map use was related to significantly greater posterior, relative to anterior, hippocampal volume in two separate samples of young adults. Further, greater reported cognitive map usage correlated with better performance on a self‐initiated navigation task. Together, these data help to advance our understanding of differences between aHPC and pHPC and the greater role of pHPC in spatial mapping.